Production of breast milk in pregnant women with and without Gestational Diabetes Mellitus - Manurung, Suryani; wati, Rizki amalia; Hariyanti, Hariyanti (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2023)
Gestational diabetes mellitus (GDM) is a health disorder associated with an increased risk of type 2 diabetes mellitus in both mother and baby. Breastfeeding is one way for mothers to reduce this risk. This study aims to determine breast milk production in GDM and non-GDM pregnant women. The research design was a prospective cohort and involved 12 pregnant women. The inclusion criteria were GDM and non-GDM pregnant women aged 28-31 weeks and willing to be respondents. The Jakarta Regional Hospital research used questionnaire instruments and breast milk production observation sheets. Chi-square statistical test analysis. The research results showed a significant relationship between the status of GDM and non-GDM pregnant women and breast milk production (P value 0.05). The maximum breast milk production of GDM pregnant women is less than non-GDM, with maximum breast milk production of 0.3cc and 0.5cc. GDM pregnant women produce lower breast milk production than non-GDM pregnant women. Breast milk production in pregnant women with GDM is slower than in pregnant women without GDM. This can be seen from the research results, which show that 58.3% of non-GDM pregnant women have expressed breast milk (on average starting at 17 weeks of gestation). Of pregnant women with GDM, only 8.3% have ever expressed breast milk (starting from the 31st week). Education on breastfeeding during pregnancy and maternal nutrition is necessary to increase maternal self-efficacy. Researchers hope to observe long-term breastfeeding expenditure from pregnancy to six months or even two years.